PAR2 Activation on Human Kidney Tubular Epithelial Cells Induces Tissue Factor Synthesis, That Enhances Blood Clotting - Iyer, Abishek; Humphries, Tyrone L. R.; Owens, Evan P.; Zhao, Kong-Nan; Masci, Paul P.; Johnson, David W.; Nikolic-Paterson, David; Gobe, Glenda C.; Fairlie, David P.; Vesey, David A. (Frontiers in Physiology, 2021)
Coagulation abnormalities and increased risk of atherothrombosis are common in patients with chronic kidney diseases (CKD). Mechanisms that alter renal haemostasis and lead to thrombotic events are not fully understood. Here we show that activation of protease activated receptor-2 (PAR2) on human kidney tubular epithelial cells (HTECs), induces tissue factor (TF) synthesis and secretion that enhances blood clotting. PAR-activating coagulation-associated protease (thrombin), as well as specific PAR2 activators (matriptase, trypsin or synthetic agonist 2f-LIGRLO-NH2 (2F), induced TF synthesis and secretion that were potently inhibited by PAR2 antagonist, I-191. Thrombin- induced TF was also inhibited by a PAR1 antagonist, Vorapaxar. Peptide activators of PAR1, PAR3 and PAR4 failed to induce TF synthesis. Differential centrifugation of the 2F-conditoned medium sedimented the secreted TF, together with the exosome marker ALG-2 interacting protein X (ALIX), indicating that secreted TF was associated with extracellular vesicles. 2F-treated HTEC conditioned medium significantly enhanced blood clotting, which was prevented by pre-incubating this medium with an antibody for TF. In summary, activation of PAR2 on HTEC stimulates synthesis and secretion of TF that induces blood clotting, and this is attenuated by PAR2 antagonism. Thrombin- induced TF synthesis is at least partly, mediated by PAR1 transactivation of PAR2. These findings reveal how underlying haemostatic imbalances might increase thrombosis risk and subsequent chronic fibrin deposition in the kidneys of patients with CKD and suggest PAR2 antagonism as a potential therapeutic strategy for intervening in CKD progression.